Observing individual children in early childhood classrooms using Optimizing Learning Opportunities for Students (OLOS): A feasibility study - Connor, Carol McDonald (Early Child Res Q, 2019)
In this study, we present a newly developed observational system, Optimizing Learning Opportunities for Students (OLOS). OLOS is designed to elucidate the learning opportunities afforded to individual children within early childhood classrooms and as they transition to formal schooling (kindergarten through third grade). OLOS records the time spent in different types of learning opportunities (e.g., play, literacy, math) and the frequency of specific discourse moves children and teachers use (child talk and teacher talk). Importantly, it is being designed to be used validly and reliably by practitioners. Using OLOS, we explored individual children’s experiences (n = 68 children in 12 classrooms) in four different types of early childhood programs; state-funded, state-funded PK serving children with disabilities, Head Start, and a tuition-based (non-profit) preschool. Results of our feasibility study revealed that we could feasibly and reliably use OLOS in these very different kinds of pre-kindergarten programs with some changes. OLOS provided data that aligned with our hypotheses and that our practitioner partners found useful. In analysing the observations, we found that individual children’s learning opportunities varied significantly both within and between classrooms. In general, we observed that most of the PK day (or half day) was spent in language and literacy activities and non-instructional activities (e.g., transitions). Very little time in math and science was observed yet children were generally more likely to actively participate (i.e., more child talk) during academic learning opportunities (literacy, math, and science). The frequency of teacher talk also varied widely between classrooms and across programs. Plus, the more teacher talk we observed, the more likely we were to observe child talk. Our long-term aim is that OLOS can inform policy and provide information that supports practitioners in meeting the learning and social-behavioral needs of the children they serve.